2021
DOI: 10.1186/s40560-021-00589-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone, ascorbic acid, and thiamine (HAT) for sepsis and septic shock: a meta-analysis with sequential trial analysis

Abstract: Background Sepsis is a primary global health threat and costs a lot, requiring effective and affordable treatments. We performed this meta-analysis to explore the treatment of hydrocortisone, ascorbic acid, and thiamine (HAT) in sepsis and septic shock. Methods We searched Ovid MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials from inception to August 14, 2021. We included randomized controlled trials (RCTs) that evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…In spite of theoretical plausibility of hydrocortisone, vitamin C, and thiamine combination therapy, our study’s results do not provide any significant survival benefit in septic shock patients, which is consistent with the results of previous RCTs [ 5 , 6 , 9 , 19 ] and meta-analyses [ 20 , 21 ]. It is worth pointing out that Marik et al [ 4 ] and Chang et al [ 22 ] highlighted that the early use of the combination therapy appeared to be associated with patients’ survival improvement.…”
Section: Discussionsupporting
confidence: 91%
“…In spite of theoretical plausibility of hydrocortisone, vitamin C, and thiamine combination therapy, our study’s results do not provide any significant survival benefit in septic shock patients, which is consistent with the results of previous RCTs [ 5 , 6 , 9 , 19 ] and meta-analyses [ 20 , 21 ]. It is worth pointing out that Marik et al [ 4 ] and Chang et al [ 22 ] highlighted that the early use of the combination therapy appeared to be associated with patients’ survival improvement.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, multiple randomized controlled trials (RCTs) evaluating the effect of intravenous (IV) vitamin C with or without hydrocortisone and thiamine have been completed. Several recently published meta-analyses (14)(15)(16)(17)(18)(19)(20) assessed the combination of hydrocortisone, ascorbic acid, and thiamine (HAT) treatment in septic patients. The results indicated that the HAT treatment improved the Sequential Organ Failure Assessment (SOFA) score and reduced the duration of vasopressor, but was not associated with lower short-term mortality.…”
Section: Introductionmentioning
confidence: 99%
“…24 Recent studies have failed to show a mortality benefit of the combination of thiamine, vitamin C with and without hydrocortisone in mortality outcomes for adults with sepsis. [64][65][66] However, in a retrospective analysis, thiamine supplementation improved survival for adults with hospital-acquired pneumonia. 67 Thiamine supplementation may yet have a role for certain types of infection, in cases when sepsis is caused by a thiamine-consuming organism or when pre-existing thiamine deficiency exists.…”
Section: Discussionmentioning
confidence: 99%